Crystalline and active additive for optimization morphology and absorption of narrow bandgap polymer solar cells. Issue 4 (17th November 2016) - Zhou, Weihua; Ai, Qingyun; Zhang, Lin; Liu, Xiangfu; Hu, Xiaotian; Chen, Yiwang
ABSTRACT: The morphology of active layer with an interpenetrating network structure and appropriate phase separation is of great significance to improve the photovoltaic performance for polymer solar cells. A highly crystalline small molecule named DPP‐TP6 was synthesized and incorporated into the narrow bandgap polymer solar cells to optimize the morphology of PTB7:PC71 BM active layer. The DPP‐TP6 small molecule was demonstrated to enhance the light absorbance of active layer and play the role of energy cascade to increase the exciton separation and charge transfer. What's more, DPP‐TP6 facilitated forming interpenetrating network structure and increasing the phase separation size of ternary blends. These phenomena lead to a higher hole mobility and a more balanced carrier mobility, so as to increase the power conversion efficiency to 7.85% at DPP‐TP6 weight ratio of 8 wt %, comparing to the pristine PTB7:PC71 BM system of 6.50%. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 726–733 Abstract : The morphology of active layer with an interpenetrating network structure and appropriate phase separation is of great significance to improve the photovoltaic performance for polymer solar cells. DPP‐TP6 could increase the power conversion efficiency (PCE) from 6.50 to 7.85% for PTB7:PC71 BM with optimized light absorption and morphology.